Phospholipid - from Model Membrane to Industrial Application - Helmut Hauser (CHIMIA)
The phospholipid bilayer has been shown to be a fundamental, structural element of biological membranes. An attempt is made here to briefly summarize the main physico-chemical properties of phospholipids necessary to understand their functional role in biological membranes. More recently lipid bilayers have become important in several areas of research for which the term «membrane-mimetic chemistry» has been coined. It comprises membrane mediated processes, e.g., membrane fusion, interfacial catalysis, energy conduction and conversion, drug delivery and targeting. In these research areas it is highly desirable to have simple, quick, and inexpensive methods for the production of closed unilamellar lipid vesicles at one’s disposal. In the second part of this review it will be shown how good use can be made of our knowledge of the physico-chemical properties of phospholipids to develop such methods. The discussion is focussed on methods of spontaneous vesiculation. In addition to fulfilling the above-mentioned criteria this new methodology has another important advantage: it allows the production of phospholipid vesicles differing widely in properties. Variables are the vesicle size and size distribution, the surface charge density, the bilayer fluidity, permeability, and stability.